Pengaruh Konten Tik Tok Terhadap Daya Serap Tik Tokers Di Dalam Memahami Materi Bahasa Indonesia Level SMA - Alfiana Sri Wahyu Wulandari; Nensy Megawati Simanjuntak; Hikmah Maulida Fitria (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
Tiktok is an application that is now widely used by the millennial generation, especially high school students. The purpose of this writing is to determine the influence of TikTok on the language development of high school students. This research uses qualitative data collection techniques or a descriptive approach. The theoretical basis and discussion comes from the results of literature research from various sources such as books, journals and articles.The research results show that the Tiktok application is one of the most influential things in language development. It cannot be denied that everything has a positive or negative impact. Therefore, parents and educators should pay more attention to elementary school students' language skills, so that their language development shows a more positive attitude.